Natural Antioxidants Dietary and Lipid Oxidation Analysis in Zebrafish (Brachydanio rerio) Tissue - ARDIANSYAH ARDIANSYAH; INDRAYANI INDRAYANI (HAYATI Journal of Biosciences, 2007)
Autoxidation of lipids is related to flesh deterioration and discoloration, as well as unpleasant flavors produced during processing and storage. This becomes a major factor determining fresh and frozen seafood products price. The aims of this research were to investigate the effect of two novel dietary supplementation antioxidants Vinlife grape seed extract and Herbalox rosemary extract on lipid oxidation during post-mortem storage of zebrafish (Brachydanio rerio) and the relationships between dietary antioxidants with the enzymatic antioxidant activities. Herbalox supplemented diet showed no harmful effects on growth or survival of zebrafish. However, the diet could not inhibit Thiobarbituric Acid Reactive Substances (TBARS) formation in zebrafish during post-mortem storage at 4 oC. Dietary Herbalox and Vinlife supplementation also showed no deleterious effects on growth or survival of zebrafish. The Vinlife supplementation efficiently suppressed TBARS formation in the zebrafish but the Herbalox supplementation. The two novel antioxidants had significant effects on catalase and glutathione S-transferase but not on glutathione peroxidase. These findings suggested that the supplementation with Vinlife was more effective than with Herbalox in inhibiting the formation of lipid oxidation products in zebrafish. Hence, Vinlife supplementation, could be a safe alternative method to improve oxidative stability of fish lipid contents. Key words: natural antioxidant, lipid oxidation, TBARS, GPx, CAT, GST